Medicinal and aromatic plants improve livelihoods in Yemen - Gotor, Elisabetta; Cherfas, J. (2012)
The aim of this brief is to analyze the impact of a set of interventions related to conservation and use of neglected and underutilized species (NUS) on people’s livelihoods. Specifically a simultaneous three-equation model of households’ participation on undertulized crops conservation and income generation activities is applied to evaluate the outcome of a pilot research project implemented by Bioversity International in Yemen between 2002 and 2005. Results generated show a relation between project participation and the perceived yield increase demonstrating the importance for farmers to actively participate in the project’s activities and subsequently apply agronomic practices learnt to improve their livelihood. The generated benefits incentivized farmers to continue to apply the interventions beyond the lifetime of the project ensuring thus a sustainable process in which exogenous interventions, once adopted by farmers become integrant part of farmer’s agronomic practices.